Theatre and the Drama of Law: A ‘Theatrical History’ of the Eichmann Trial - Michael Bachmann (Law Text Culture, 2010)
In his seminal study, The Seventh Million, historian Tom Segev (1993) examines how the changing perceptions of the Holocaust relates to the ways in which Israelis understand themselves, their state, and its connection to the Diaspora. Segev’s cultural history begins with a phone call he describes as if it were a direct link to the past. The call, made in 1987, is to writer and Holocaust survivor Yehiel De-Nur, who answers in a ‘hushed, choked voice’ (Segev 1993: 3). Segev wants to ask him for an interview. Upon hearing his voice, however, Segev is instantly taken back, as it were, to the moment twenty-six years ago when he first heard the Holocaust survivor speak. In 1961, De-Nur was one of the witnesses at the trial against Adolf Eichmann in Jerusalem. His testimony has become famous for the fact that he could utter a mere few sentences before fainting.